Envoy: A Review of Literature and Art and Post-War Irish Culture - LINNIE, CONOR (Trinity College Dublin. School of English. Discipline of English, 2018)
This thesis examines the Irish literary and visual art magazine Envoy: A Review of Literature and Art (1949-1951). It establishes the magazine as a key post-war site of transnational aspiration and activity at the beginning of a period of transition in Irish society toward greater international involvement and integration. The thesis argues that Envoy significantly contributed to the development of a range of cross-border, archipelagic, continental, and transatlantic connections and networks that variously stimulated, challenged, and ultimately expanded the dimensions of Irish cultural discourse and production.
APPROVED
Keywords: Irish Poetry; Irish Visual Art; Irish Art; Irish Periodical Culture; Envoy: A Review of Literature and Art; Little Magazines; Post-War Irish Culture; Irish Literature; Patrick Kavanagh; James Joyce; Nano Reid; Twentieth-Century Irish Literature; Mid-Twentieth-Century Irish Literature; Twentieth-Century Irish Poetry; Irish Modernism; Twentieth-Century Irish Art; Samuel Beckett; Art Writing; The Bell